Arte, educação e literatura: o regionalismo universal de Eli brasiliense e frei confaloni - ROSA, Denilson Pereira (2012)
This dissertation, developed at the Research Line: Culture and Educational Processes Program of Graduate Studies in Education of the Federal University of Goias, addresses the issue of intrinsic relations between education, visual arts and literature. To develop it we chose a qualitative approach, similar to bibliographic research using methodological assumptions of the historical survey of art and culture of Goias in an aesthetic standpoint and also local. We analyzed Eli Brasiliense novels and works of Frei Nazareno Confaloni, looking for ideas about man and nature, the world of school, modern art, the popular religion, work and courage of the frontiersman and his connection to the land. For this analysis, we used the references of Barbosa, Candido, Palacin, Olives, Borges, Cavalcanti and Sabino Junior. In conclusion, it was realized that the culture, like possibility of education, goes beyond the art education of formal teaching, and yet the languages of literature and the visual arts are interrelated and are essential in human development.